Evaluation One Village One Product at Loram Wetan Village Kudus Regency Year of 2014-2017 - Faisol, Andre; ., Kushandajani (Journal of Politic and Government Studies, 2018)
This study was aimed to evaluate one village one product program (OVOP) that is implemented by DISNAKERPERINKOP and UKM Kudus Regency in 2014-2017. The teory that uses in this study is four evaluation indicators which are: Indicator Input, Proses, Output, and Outcome. This study used a qualitative method with descripetive analysis. The primary data in this study derived from interviews data from informants who considered have knowledge about program that implemented at Loram Wetan Village, while the secondary data derived from documents, internet, and anything else that relate to this study.            The survey shows that the program has been well implemented accordance to the program planning. Since 2014-2017 year the implement program already can accommodate 36 craftmans groups at Loram Wetan Village. Impact of this program to the craftmans that perceived their business network help the craftmans to share information about how to solve problem they had also cooperate each other and the program have potency to absorb labor with tailor mastery.            Based on survey result this study conclusion is from four evaluation indicators show if indicator input not well implemented caused lack of human resource and lack of capital. OVOP Program that implemented at Loram Wetan Village in 2014 shows two obtacles which are: lack of labor with tailor mastery and lack of capital resouce to increase the production. Keyword: Evaluation, Program, OVOP